Description of physical fitness in Argentinean under-15 judokas (Revista de Artes Marciales Asiáticas, 2024)
Normative tables are valuable tools for training planning and talent selection in judo. However, normative tables for athletes under the age of 15 have not been found. The aim of this study was to describe the physical fitness of under-15 judokas in Argentina and to elaborate normative tables based on physical tests, including maximum time in suspension with judogi, maximum repetitions of pull-ups, vertical jump test, and Special Judo Fitness Test. Records obtained in 2019 from 212 judokas aged 13 and 14 were analysed for each physical test. Normative tables were created using a percentile scale, classifying as: very poor (